THU0369 IL-17A+ and IL-22+ T Cells Increase during anti-TNFα Treatment in Spondyloarthritis – A Link To Radiographic Progression?. (15th July 2016) - Andersen, T.; Hvid, M.; Kragstrup, T.; Gleerup, H.; Jurik, A.G.; Østgård, R.; Deleuran, B.
Abstract : Background: The pro-inflammatory Th17 associated cytokines IL-17A and IL-22 have been proposed as important mediators in spondyloarthritis (SpA). Treatment of SpA has been improved dramatically with the introduction of tumor necrosis factor (TNF)α inhibitors. Despite good clinical efficacy, anti-TNFα fail to affect bone formation and radiograpchic progression in SpA. Th17 cells and cytokines might be involved in this lack of response to anti TNF-α antibodies. Objectives: To investigate the association of Th17 cells with changes in clinical and MRI activity in SpA patients treated with anti-TNFα. Furthermore, to investigate the involvement of the Th17 cytokines IL-17A and IL-22 on bone anabolic pathways in SpA. Methods: Percentage of IL-17A and IL-22 producing T cells were assessed in peripheral blood mononuclear cells from 30 SpA patients at baseline, after 12 and 52 weeks of anti-TNFα therapy using intracellular flow cytometry. Clinical activity was evaluated using the Ankylosing Spondylitis Disease Activity Score (ASDAS) and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). MRI grading was performed on the whole spine and in the sacroiliac joints (SIJ). Correlation analyses were performed to investigate the association between percentages of Th17 cells and disease progression during the course of treatment. Normal human osteoblasts and fibroblast like synoviocytes (FLS) were stimulated with IL-17A, IL-22, TNFα and supernatants from CD4+CD45RO+CCR6+ cells to determine the bone modulatory activity of Th17 cytokines. Results: Percentages of IL-17A producing and IL-22 producing, and CCR6 expressing CD4+CD45RO+ T cells were increased at baseline compared with healthy controls. These subsets increased during 52 weeks of anti-TNFα therapy, despite clinical response with the composite scores ASDAS decreasing from 3.6 (3.0–4.0) to 1 (0.5–1.9) and BASDAI decreasing from 63.50 (52–71) to 15 (3- 31). High baseline percentages of IL-17A and IL-22 producing CD4+CD45RO+ T cells correlated with greater improvement in ASDAS and BASDAI score. Both baseline percentages of IL-17A and IL-22 producing CD4+CD45RO+ T cells were associated with increased levels of chronic MRI changes at baseline (both p<0.05). Additionally, IL-17A producing CD4+CD45RO+ T cells at baseline were associated with chronic MRI changes in the SIJ at 12 months (p<0.01). IL-17A, IL-22 and TNFα stimulation increased mineral deposition from normal human osteoblasts. IL-22 in combination with TNFα inhibited the secretion of Dkk-1 from SpA FLS, whereas neither TNFα nor IL-17A were able to affect Dkk-1 secretion from SpA FLS. Conclusions: Th17 cells increased during anti-TNFα therapy, regardless of clinical improvement. Th17 cell percentages at baseline predict clinical response and are associated with chronic MRI changes at baseline and outcome at 52 weeks. Not only IL-17A, but also IL-22 are able to affect bone formation and bone remodelling pathways, but only IL-22 induce Dkk-1 in FLS. Hereby, the consistently elevated percentages of Th17 cells, despite good disease control in this group of SpA patients, could provide a link to the ongoing ectopic bone formation seen in SpA. Disclosure of Interest: T. Andersen Grant/research support from: Janssen, M. Hvid: None declared, T. Kragstrup: None declared, H. Gleerup: None declared, A. Jurik: None declared, R. Østgård: None declared, B. Deleuran: None declared